Expression and Characterization of Amylomaltase Gene Involved in the Large-Ring Cyclodextrin and Isomalto-Oligosaccharide Production - Kaulpiboon, Jarunee; Poomipark, Natwadee; Watanasatitarpa, Suphatra (Science & Technology Asia, 2016)
Amylomaltase catalyzes a cyclization reaction to produce large-ring cyclodextrins (LR-CDs) from starch, which can be used in pharmaceutical industry. In this study, the amylomaltase gene was sub-cloned from p17bAMY recombinant plasmid into a pET-19b vector containing an NH2-terminal His-tag. The maximum expression was obtained when the recombinant cells were cultured at 37oC for 4 h with 0.8 mM IPTG. The amylomaltase was purified up to 47-fold by Ni-NTA column and the specific activity of enzyme was 122 units/mg protein with a 44% yield. The relative molecular mass of purified enzyme was 60 kDa by 10% SDS-PAGE. In addition, the enzyme prefers to use pea starch as a substrate in the production of LR-CDs with degrees of polymerization from 23-37 glucose units. Besides LR-CD production, amylomaltase when used in co-action with transglucosidase could also produce long chain isomalto-oligosaccharides (IMOs) from pea starch for serving as prebiotic substance.